2018
DOI: 10.1039/c8ce00940f
|View full text |Cite
|
Sign up to set email alerts
|

Thermosalient effect of two polymorphs of a diketopyrrolopyrrole dye with different crystal systems and molecular arrangements

Abstract: Two polymorphs of a diketopyrrolopyrrole dye, one yellow and the other orange, were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…corresponds to the melting point, whereas the first peak is relatively broad, corresponding to a polymorphic phase transition. This polymorphic phase transition indicates the thermosalient effect accompanied by mechanical behaviour, and the PXRD result of PR3Y right after the phase transition coincided with the results obtained for PR3O (So et al, 2018). This suggests that PR3O is thermodynamically more stable after the phase transition and the two polymorphs are in an enantiotropic relationship with each other.…”
Section: Figuresupporting
confidence: 82%
See 3 more Smart Citations
“…corresponds to the melting point, whereas the first peak is relatively broad, corresponding to a polymorphic phase transition. This polymorphic phase transition indicates the thermosalient effect accompanied by mechanical behaviour, and the PXRD result of PR3Y right after the phase transition coincided with the results obtained for PR3O (So et al, 2018). This suggests that PR3O is thermodynamically more stable after the phase transition and the two polymorphs are in an enantiotropic relationship with each other.…”
Section: Figuresupporting
confidence: 82%
“…6 resulted in two different combinations of concomitant polymorphs. So et al (2018) and its chemical structure was confirmed by conventional analytical techniques. The crystallization of PR3C was carried out by liquid-liquid diffusion and the liquid-vapour diffusion method using a combination of various good (highly soluble) and poor (insoluble or less soluble) solvents ( Table 1).…”
Section: Tablementioning
confidence: 84%
See 2 more Smart Citations
“…The effect was first noted in 1983, and after a long hiatus, it was explored in greater detail in the anticholinergic agent oxitropium bromide in 2010 . Encouraged by these studies, over 20 new examples have been reported in the last decade that are categorized in three classes based on their structures, with a number of notable reports of serendipitous observations increasing in the past several years . It has also been demonstrated that the rates of the TS phase transitions are several orders of magnitude faster than other, more common solid–solid transitions .…”
Section: Introductionmentioning
confidence: 99%